Bingo Game as a Creative Strategy for Arabic Vocabulary Mastery: Permainan Bingo sebagai Strategi Kreatif Penguasaan Kosakata Bahasa Arab - Khusna, Asmaul (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Vocabulary mastery is a central component in Arabic language learning, yet many elementary students struggle to remember and apply new words effectively. Specific background: Traditional approaches relying on lectures and repetition often fail to maintain engagement, limiting vocabulary retention. Knowledge gap: Few studies have empirically explored game-based strategies, particularly the Bingo method, for Arabic vocabulary learning at the elementary level. Aims: This study examined the role of the Bingo game, assisted by card media, in supporting Arabic vocabulary mastery among fifth-grade students at Madrasah Ibtida’iyah Darut Taqwa. Results: Findings revealed a significant improvement in students’ scores—from an average of 43.33 to 54.66—with a gain score of 11.33 categorized as high. The paired-sample t-test confirmed statistical significance (p < 0.001), indicating that students demonstrated higher engagement and retention after the intervention. Novelty: Integrating Bingo into vocabulary instruction provides a playful, social, and interactive learning atmosphere aligned with the Merdeka Belajar framework. Implications: The study contributes to curriculum design by offering an innovative learning model that can be further developed digitally to support technology-integrated Arabic learning in the 21st century. Highlights Game-based learning fosters active participation and enjoyment in Arabic vocabulary classes. Bingo cards enhance students’ memory and comprehension of new Arabic words. Findings align with the Merdeka Belajar vision for creative, student-centered education. Keywords Arabic Vocabulary, Bingo Game, Game-Based Learning, Elementary Education, Merdeka Belajar